Pathophysiological mechanisms of statin‐associated myopathies: possible role of the ubiquitin‐proteasome system. Issue 5 (2nd August 2020) - Sahebkar, Amirhossein; Cicero, Arrigo F.G.; Di Giosia, Paolo; Pomilio, Irene; Stamerra, Cosimo Andrea; Giorgini, Paolo; Ferri, Claudio; von Haehling, Stephan; Banach, Maciej; Jamialahmadi, Tannaz
Abstract : Background: Statins are the cornerstone of pharmacotherapy for atherosclerotic cardiovascular disease. While these drugs are generally safe, treatment adherence is not optimal in a considerable proportion of patients because of the adverse effects on skeletal muscles in the forms of myopathy, myalgia, muscular pain, nocturnal muscle cramping, weakness, and rare rhabdomyolysis. Methods: For the purpose of this narrative review, we searched for the literature suggesting the involvement of the ubiquitin–proteasome system in the development of statin–induced myopathy. Results: Statins have been shown to up–regulate the expression of the muscle–specific ubiquitin–proteasome system as the major non–lysosomal intracellular protein degradation system. It has been postulated that statins may provoke instability in the myocyte cell membrane when subjected to eccentric exercise stress, triggering activation of intracellular proteolytic cascades and changes in protein degradation machinery. This is accompanied by the up–regulation of a series of genes implicated in protein catabolism, in addition to those of the ubiquitin–proteasome system. Conclusions: Based on the available literature, it seems that the involvement of ubiquitin–proteasome system is potentially implicated in the pathophysiology of statin–induced myopathy.